Histological and morphological studies of the endocrine organs of xenopus laevis - Rimer, Gladys E J (Division of Physiological Sciences, 2020)
Xenopus Laevis has provided, during the last ten years, the basis of a growing body of physiological enquiries initiated by Jolly's research on reflex action. Its viability in the laboratory and amenability to operative procedure in particular, make it a peculiarly suitable object for investigation. It is regrettable therefore, that existing literature on the anatomy of Xenopus has been directed to elucidating those characteristics which are of especial interest to the Systematists and Morphologists rather than detailed information of a type which is essential to operative procedure. There is in particular no extant account of the endocrine system of Xenopus, although it is evident from superficial inspection that the suprarenal complex differs from that of the more familar Anura. The present enquiry concerns the Thyroid Gland, Pituitary and Epiphyseal Complexes with some observations concerning the possible occurrence of chromophil cells in the kidney of Xenopus laevis. The data have been placed on record specifically and constitution of these organs in physiological operations.